Bacteriocinogenic probiotics as an integrated alternative to antibiotics in chicken production - why and how?. Issue 31 (1st November 2022) - Lone, Ayesha; Mottawea, Walid; Mehdi, Youcef; Hammami, Riadh
Abstract: The misuse of antibiotics in the livestock industry has played an important role in the spread of resistant superbugs with severe health implications for humans. With the recent ban on the use of antibiotics in poultry and poultry feed in Canada and the USA, poultry farmers will have to rely on the use of alternatives to antibiotics (such as feed acidifiers, antibodies, bacteriophages, antimicrobial peptides, prebiotics, and probiotics) to maintain the same productivity and health of their livestock. Of particular interest are bacteriocinogenic probiotics, that is, bacterial strains capable of producing bacteriocins that confer health benefits on the host. These bacterial strains have multiple promising features, such as the ability to attach to the host mucosa, colonize, proliferate, and produce advantageous products such as bacteriocins and short-chain fatty acids. These not only affect pathogenic colonization but improve poultry phenotype as well. Bacteriocins are antimicrobial peptides with multiple promising features such as being non-harmful for human and animal consumption, non-disruptive to the host microbiota eubiosis, non-cytotoxic, and non-carcinogenic. Therefore, bacteriocinogenic probiotics are at the forefront to be excellent candidates for effective replacements to antibiotics. While evidence of their safety and effectiveness is accumulating in vitro and in vivo in inhibiting pathogens while promoting animal health, their safety and history of use in livestock remains unclear and requires additional investigations. In the present paper, we review the safety assessment regulations and commercialization policies on existing and novel bacteriocinogenic and bacteriocin products intended to be used in poultry feed as an alternative to antibiotics.